Emotional relevance and prejudice: testing the differentiated effect of incidental disgust on prejudice towards ethnic minorities - Pascal, Emilia; Holman, Andrei Corneliu; Miluț, Felicia Mihaela (Frontiers in Psychology, 2023)
Past research has highlighted spill-over effects of negative emotions on prejudice, stereotypes, and discrimination of minorities. Using an experimental design, our study aimed to examine the specificity of these effects as determined by the relevance of the emotion currently experienced to the prejudiced out-group. Our assumption was that negative emotions increase prejudice only toward out-groups that elicit the same specific emotion, i.e., anger would increase prejudice towards anger-relevant groups, and disgust towards disgust-relevant groups. To test this hypothesis, we investigated the effects of incidental disgust on the evaluation of two minorities, one usually associated with disgust (the Roma minority) and one usually associated with anger (the Hungarian minority). We used a 2x2 between-subjects experimental design whereby we manipulated the emotion experienced by the participants (disgust versus neutral) and the target they evaluated (Romani or Hungarian minority). We tested the effects of these manipulations on three aspects of prejudice toward the target group: cognitive, affective, and behavioral. The results support the specificity of the spill-over effect, by showing that incidental disgust increased prejudice only towards the disgust-relevant target, namely the Roma minority, and that the intensity of this emotion mediates this effect. Moreover, incidental disgust increased not only the negative emotions associated with the Romani (i.e., the affective component) but also the negative cognitions associated with them and the desire to maintain an increased social distance (i.e., behavioral prejudice).